Identifying Purse Seine Vessel Operations Through Machine Learning Models for Better Spatial Fishing Effort Estimates - Joan Sala‐Coromina; Mireia Silvestre; Felipe H. Coutinho; Marta Carreton; Marta Blanco; Jordi Ribera‐Altimir; Laura Recasens; Joan B. Company (Fish and Fisheries, 2026)
Spatial fisheries management requires precise, spatial explicit information on species distribution and fishing impacts. In the NW Mediterranean, the distribution of small pelagic fish (SPF) stocks is currently assessed through annual acoustic surveys. Although accurate, these surveys might lack the temporal resolution needed to capture population dynamics. Analysing fishing fleet spatial behaviour allows estimation of fishery impacts and can uncover patterns of target species at high temporal resolution. In this study we apply machine learning models to classify multiple vessel operations on vessel monitoring system (VMS) data for purse seiners targeting SPF populations. Three main vessel operations were defined based on onboard observations: Fishing, Tracking and Cruising. Then, random forest models were trained to predict vessel operations in VMS data using seven predictive variables. Machine learning models highly improved predictions accuracy (81% and 73%) compared to a classical speed filter method (60%). Fishing effort metrics were computed and compared across predictive methods resulting in a high overestimation of fishing activities when using a speed filter approach. The effect of spatial resolution in fishing effort metrics was also tested revealing a good performance of random forest predictions at 2–3 km 2 . The methods developed allow quantification of three vessel operations activities improving purse seiners effort metrics compared to classical binary (fishing/non‐fishing) approaches. Consequently, spatially explicit catch per unit effort (CPUE) estimates for SPF will also be improved as well as the accuracy of the information needed for spatially manage of this fishery.

Baseline data of the marine recreational fisheries in the NW Mediterranean Sea: finding the variable that drives the catch - Marta Pujol-Baucells; Carlota Mateu-Pinilla; Marta Blanco; Marta Carreton; Laura Recasens; Joan B. Company; Eve Galimany (Frontiers in Marine Science, 2025)
Recreational fishing is an increasingly popular leisure activity on a global scale, with catches that may surpass those of commercial fisheries. However, the lack of comprehensive and standardized data hinders accurate assessment of its ecological impact. This study investigates the species composition across three variables including fishing modalities (shore angling, boat angling, and spearfishing), zone and season along the NW Mediterranean coast. Species identification and number of individuals caught data were obtained through onsite surveys conducted between 2020 and 2023. The results reveal significant differences in catch composition among modalities, as well as across spatial and seasonal scales. However, modality exhibited the greatest differentiation in catch composition compared to the other two variables. Then, regarding modality, boat angling and spearfishing yield the highest catch rates but boat angling had the greatest number of species (i.e., 69). However, species composition characterized the catches of each modality. Specifically, Dicentrarchus labrax was more frequently fished by shore anglers, Loligo vulgaris by boat anglers, and Mullus surmuletus by spearfishers. Currently, there is a need to develop and reinforce marine recreational fisheries sustainable management practices at a regional scale. In the study area, our findings suggest that fishing modality is the main driver to consider when developing sustainable management strategies and the conservation of coastal marine biodiversity.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Understanding the spatio-temporal variability of fisheries data for better bottom trawling management practices in the Catalan margin (NW Mediterranean Sea) - Marta Carreton; Eve Galimany; Marta Blanco; Mariona Garriga-Panisello; Ana I. Colmenero; Marc Balcells; Ferran Bustos; Mireia G. Mingote; Cristina López-Pérez; David Nos; Xènia Puigcerver-Segarra; Marta Pujol-Baucells; et al. (Marine Policy, 2025)

ROV-based monitoring of passive ecological recovery in a deep-sea no-take fishery reserve - Maria Vigo; Joan Navarro; Jacopo Aguzzi; Nixon Bahamón; José Antonio García; Guiomar Rotllant; Laura Recasens; Joan B. Company (Science of The Total Environment, 2023)

Regional dynamic co-management for sustainable fisheries and ecosystem conservation: a pilot analysis in the Catalan Sea - Jean-Noël Druon; Josep Lloret; Joan Sala-Coromina; Laura Recasens; Sílvia Gómez; Laura Fontán Bouzas; Jordi Guillen; Sergi Tudela (Frontiers in Marine Science, 2023)
The complexity of coastal fisheries, which often involve many gears with cross-impacts on various species and life stages, requires a management system that is able to integrate these multiple interactions in order to gradually achieve sustainability. In this paper, we argue that regional co-management can appropriately address the complex interactions between fisheries, including those with other potentially conflicting human activities. Our results, notably obtained through a questionnaire to local fishers’ representatives mainly on bottom trawl fisheries in the Catalan Sea region, show, however, that improved mutual understanding through effective communication and long-term collaboration between stakeholders, and in particular between fishers and scientists, is essential to ensure the successful implementation of fisheries co-management. In addition to balancing the voices of the many stakeholders, co-management needs to be further improved by developing multi-species, multi-gear and multi-use approaches to the oceans. This improvement could in turn support the effectiveness of co-decisions, as they would be based on the recognised administrative structure of co-management committees and sound scientific guidance that addresses both ecosystem protection and sustainable fisheries profitability. Dynamic management over time and space, using real-time essential fish habitat from operational oceanography, can help to make the co-management process more robust by improving collaboration between stakeholders and the effectiveness of measures in a changing environment. The decision-making, social and ecological components are described as integral and dependent parts of the co-management system, with priority given to mutual understanding between stakeholders. This integrated co-management framework is flexible enough to take into account regional complexity, but also national legislation and the EU Common Fisheries Policy, which all promote sustainable use of the oceans and protection of the ecosystem.

Spatial distribution of the demersal chondrichthyan community from the western Mediterranean trawl bycatch - David Ruiz-García; Juan A. Raga; David March; Ana I. Colmenero; Federico Quattrocchi; Joan B. Company; Laura Recasens; Claudio Barría (Frontiers in Marine Science, 2023)
Introduction Chondrichthyans (sharks, batoids and chimaeras) play key roles in the regulation of marine food webs dynamics. However, more than half of the assessed species in the Mediterranean are threatened, primarily by fishing pressure and compounded by habitat degradation and climate change. Nevertheless, there is an important knowledge gap in identifying the underlying drivers of their community structure and spatial distribution. Methods and Results We provide insights into the current bycatch rates of chondrichthyans in the western Mediterranean commercial bottom trawling fishery by accurately depicting the unaltered practices of the local fleet. A total of 17 species were recorded in the studied fishing grounds (ranging from 50 to 800 m deep), including 7 sharks, 9 batoids, and 1 chimaera, although the total catch was dominated by few species. Furthermore, we tested the effect of environmental and fishing-related factors on multiple community descriptors by using analysis of community structure (multidimensional scaling and analysis of similitude) and generalized linear mixed models to further understand the drivers of the chondrichthyan community distribution and structure. This study revealed the importance of combining environmental and anthropogenic drivers to further understand the spatial distribution patterns of chondrichthyan communities. Our results indicate that depth was the main driver of the community structure, with deeper areas within the fishing grounds hosting a higher diversity. Sea bottom temperature and substrate type also influenced the distribution of the community, with substrate effects changing depending on the intensity of fishing pressure. In all cases, density, biomass, and diversity of chondrichthyans were negatively impacted by increasing fishing effort. Discussion Understanding the drivers of the structure and distribution of the chondrichthyan community is crucial to understand the potential impacts that increased fishing pressure, habitat loss and global change may entail. The ongoing challenges that the Mediterranean chondrichthyans and their ecosystems are facing highlights the need for continued monitoring and improved chondrichthyan-focused fisheries management.

Characterization of discards along a wide bathymetric range from a trawl fishery in the NW Mediterranean - Marta Blanco; David Nos; Antoni Lombarte; Laura Recasens; Joan B. Company; Eve Galimany (Fisheries Research, 2023)

Cyclic fluctuations of blue whiting ( Micromesistius poutassou ) linked to open‐sea convection processes in the northwestern Mediterranean - Paloma Martin; Francesc Maynou; Laura Recasens; Ana Sabatés (Fisheries Oceanography, 2016)
In the Mediterranean, blue whiting, Micromesistius poutassou , constitutes a traditional fisheries resource. Over several decades, blue whiting landings in the Catalan coast (northwestern Mediterranean) have displayed cyclical variations, of c . 6 yrs, slightly decreased to five in the last two decades, as shown through wavelet analysis. These fluctuations have persisted under very different levels of fishing effort. This study evaluates the hypothesis that deep‐water formation in the adjacent Gulf of Lions, and the enhanced primary productivity related to it, determines recruitment strength in blue whiting that results ultimately in the observed periodicity of the blue whiting landings. The link between landings and environmental drivers was explored using lagged cross‐correlations, with 0‐ and 1‐yr lag. The variables considered included large‐scale indices [North Atlantic Oscillation (NAO) and the Atlantic Multi‐decadal Oscillation (AMO)], Mediterranean climate indices [MO and Western Mediterranean Oscillation (WeMO)], and variables defining the local environmental conditions in the northwestern Mediterranean (sea‐air heat flux, winter air temperature anomaly and Rhône river runoff). Significant correlations were only found between landings (1961–2011) and sea‐air heat flux, which is generally taken as an indicator of processes of deep water convection, at 0 and 1‐yr lag. These results suggest that the observed fluctuations in blue whiting landings respond to oceanographic processes taking place in the Gulf of Lions.

Combining GIS and GAMs to identify potential habitats of squid Loligo vulgaris in the Northwestern Mediterranean - Pilar Sanchez; Montserrat Demestre; Laura Recasens; Francesc Maynou; Paloma Martin (Hydrobiologia, 2008)